Aplicativo para aquisição, processamento e armazenamento de dados de receptores GNSS e sensores analógicos - Campos, Fernando Henrique [UNESP]; Padovani, Carlos Roberto Pereira [UNESP]; Marasca, Indiamara [UNESP]; Guerra, Saulo Philipe Sebastião [UNESP]; Lanças, Kléber Pereira [UNESP] (My University, 2013)
The informatics technology provides benefits to various branches of activity, being one of them the precision agriculture. Precision Agriculture can be defined as the union of technologies that aim to reduce agroforestry production losses, increase rural economic return and reduce environmental impacts. In this context informatics technology among other advantages, allows the acquisition, processing and storage of data obtained in the field. The automatic data logging helps in the elimination of human error in reading and typing, reduction data loss, combating lack of synchronism between the readings various instruments, besides guaranteeing different frequencies reading ensuring data integrity. This study aimed to develop a software dedicated to UMAS (Mobile Unit Soil Sampling) whose main functions are to accomplish acquisition, processing and storage of data from analog sensors (load cell and potentiometer) and GNSS receivers. The application was called "PROCOLD" (Data Collection Program). For its development was used programming language - Microsoft Visual Basic 2010. The results showed that the "PROCOLD" successfully performed data: acquisition, processing and storing from up to four GNSS receivers simultaneously and of the analog sensors at the same time. The "PROCOLD" generated reliable information for the preparation of reports, and addition, the data obtained by the GNSS receivers, after processed and stored by the "PROCOLD" could be easily applied in the preparation of thematic maps georeferenced.

A tecnologia na área de informática oferece benefícios a diversos ramos de atividade, sendo um deles a agricultura de precisão. A agricultura de precisão pode ser definida como a utilização de tecnologias com o objetivo de reduzir perdas na produção agroflorestal, aumentar o retorno econômico do meio rural e reduzir os impactos ambientais. Nesse contexto, a informática entre outras vantagens, possibilita a aquisição, processamento e o armazenamento informatizado dos dados obtidos no campo. O registro automático de dados proporciona a eliminação de erros humanos de leitura e digitação, redução de perda de dados, combate à falta de sincronismo nas leituras entre vários instrumentos, além de garantir diferentes frequências de leitura assegurando a integridade dos dados. O presente trabalho objetivou o desenvolvimento de um software dedicado a UMAS (Unidade Móvel de Amostragem do Solo) cujas principais funções são realizar a aquisição, processamento e armazenamento dos dados provenientes de sensores analógicos (célula de carga e potenciômetro) e receptores GNSS. O aplicativo foi denominado “PROCOLD” – Programa de Coleta de Dados. Para seu desenvolvimento, foi utilizada a linguagem de programação – Microsoft Visual Basic 2010. Os resultados mostraram que o “PROCOLD” realizou com sucesso a aquisição, processamento e armazenamento dos dados simultâneos de até quatro receptores GNSS independentes e dos sensores analógicos no mesmo instante. O “PROCOLD” gerou informações confiáveis para a elaboração de relatórios, além disso, os dados obtidos através dos receptores GNSS, após processados e armazenados pelo “PROCOLD” puderam ser facilmente aplicados na elaboração de mapas temáticos georreferenciados.
Software for data acquisition, processing and storage of GNSS receivers and analogical sensors
Keywords: Precision Agriculture; Visual Basic; Application; Agricultura de precisão; Visual Basic; Software